1996
DOI: 10.1111/j.1469-8137.1996.tb01919.x
|View full text |Cite
|
Sign up to set email alerts
|

Does temperature stress induce nectar secretion in Mediterranean plants?

Abstract: SUMMARYWe Studied the effect of temperature on nectar secretion in Thymiis capitatus, a typical labiate of phrygana (i,e, the garrigue of the East Mediterranean Basin). Experiments were carried out at controlled temperatures in a climatic chamber. We measured the nectar standing crop of the flowers at the end of the first day of their anthesis. All nectar values (i,e, volume per flower, sugar content and concentration) increased witb temperature up to 38 °C, as long as the plants were not water stressed. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 15 publications
2
76
0
6
Order By: Relevance
“…The heat tolerance of Ziziphus has been reported by Orwa et al (2009). Petanidou and Smets (1996) reported a positive correlation between all nectar values (i. e. volume per flower, sugar content and concentration) and temperatures in the Mediterranean up to 38°C for Thymus capitatus. Crystallization of the nectar on the surface of the flower may negatively affect the efficient collection of nectar by legitimate pollinators including honeybees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat tolerance of Ziziphus has been reported by Orwa et al (2009). Petanidou and Smets (1996) reported a positive correlation between all nectar values (i. e. volume per flower, sugar content and concentration) and temperatures in the Mediterranean up to 38°C for Thymus capitatus. Crystallization of the nectar on the surface of the flower may negatively affect the efficient collection of nectar by legitimate pollinators including honeybees.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted on different species to quantify nectar secretion and to explore its dynamics, mainly in relation to pollination biology, phenology and biophysical factors of the environment (e.g. Petanidou and Smets, 1996;Castellanos et al, 2002;Galetto and Bernardello, 2004). Quantitative studies on nectar secretion of melliferous plants include those of Pesti (1976), Mohr and Jay (1990), Nepi et al (2001), Farkas and Orosz-Kovács (2003), Horváth and Orosz-Kovács (2004) and Zajácz et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…An Finally, climate change may influence the availability of floral rewards such as nectar to pollinators, since it alters the availability of water (Willmer and Corbet, 1981;Petanidou and Smets, 1996), which in return can decrease pollinator foraging efficiency (Golubov et al, 1999). Petanidou and Smets (1996) showed that the floral nectar secretion of Thymus capitatus (L.) Hoffmanns. & Link, a widespread and characteristic plant of the Mediterranean, is significantly reduced at relatively high temperatures (> 32.5ºC).…”
Section: In the Aegeanmentioning
confidence: 99%
“…7 et Tab. 2 ;Findlay et al, 1971 ;Nicolson, 1995), confirmant ce qui a déjà été observé chez plusieurs espèces sur le taux de sécrétion apparent (Huber, 1956 ;Villarreal et Freeman, 1990 ;Petanidou et Smets, 1996 ;Pacini et Nepi, 2007 ;Petanidou, 2007 ;Takkis et al, 2015).…”
Section: Discussionunclassified